1987
DOI: 10.1177/002199838702100104
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Longitudinal Splitting in Unidirectional Composites

Abstract: An experimental study was conducted to determine the fracture behavior of center- notched, unidirectional graphite/epoxy laminates when subjected to tensile loading. The actual behavior is compared to the behavior predicted by a mathematical model based on classical shear-lag assumptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…7a). According to several reports [33][34][35], at tension the critical stress at which splits appear near a hole coincides with that for splitting near a crack. Splitting stress in both cases is described by linear fracture mechanics.…”
Section: The Effect Of Circular Holessupporting
confidence: 55%
See 1 more Smart Citation
“…7a). According to several reports [33][34][35], at tension the critical stress at which splits appear near a hole coincides with that for splitting near a crack. Splitting stress in both cases is described by linear fracture mechanics.…”
Section: The Effect Of Circular Holessupporting
confidence: 55%
“…According to WoUa and Goree [34], fractographic analysis of the fracture surface of individual fibres in a kink allows one to conclude whether the final step of a failure is a result of tension, compression or bending of the fibres. If parallel fracture lines are detected upon the facets of single fibres in a kink, it can be concluded [38] that finally a fracture of all types of fibre in a kink is caused by their bending.…”
Section: Fracturementioning
confidence: 99%
“…The magnitudes and length scale of overloads in fibres adjacent to a cluster of contiguous breaks, combined with the strength statistics of the fibres at this characteristic length scale, determine the transverse growth of the cluster. The stress distribution at a break depends on the existence and growth of fibre/matrix debonding, which is often the precursor to longitudinal splitting [8][9][10]. While several theoretical studies have attempted to explain these phenomena [11][12][13][14][15], little has been substantiated experimentally about the constitutive behaviour and the mechanisms of debonding at the length scale of a fibre break, especially in the presence of other closely spaced fibres.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is shown in Figures 1 and 2, which indicates that the traditional shear-lag analytical method is not capabile of accounting for the stable longitudinal split of unidirectional composites. Wolla and Goree [14,15] also drew the same conclusions as us from their study of unidirectional composites with a center penetrating crack. It is suggested that a successful predictive method for the failure of composites must contain a suitable mathematical model into which the main damage factors are introduced, and a reasonable fracture criterion that can describe and control the distinct process of composites failure.…”
mentioning
confidence: 61%
“…A large number of experiments and numerical simulations [12][13][14][15] on the split failure of unidirectional composites with a crack or a surface notch, suggested that the reason for the disagreement between the experimental results and the numerically predicted ones may be that the effects of matrix yield, fiber bridging, and friction across longitudinal splitting surfaces are not taken account in the traditional shear-lag model. These factors cause a delay effect for split growth.…”
Section: Delay Effect Of Splitting Growthmentioning
confidence: 99%